Le Corbusier. Streets, promenades, scenes and artefacts. Issue 2 (2nd April 2016) - Monteys, Xavier; Fuertes, Pere
Abstract: The relationship of Le Corbusier with the street is complex and sometimes contradictory. young Jeanneret seems to be persuaded by certain sites, which we may define as urban scenarios, during his visits to cities like Istanbul in his formative years. Unlike his hometown La Chaux-de-Fonds – identified by a regular set of streets – these places may have been a picturesque coun- terpoint activated by a significant topography. Streets meandering along a set of 'Dom-ino' houses in the Oeuvre complete, as the tracking rails of a long shot recording, offer a changing viewpoint that may be considered in relation with such casual arrangements. The claim to kill the 'rue corridor' made in Précisions, together with his later writings, deeply contrast with his own comments on an empty Paris in the summer of 1942 – as published in Les Trois Établissements Humains – praising the same streets he pretended to erase by means of operations like the 'Ilôt Insalubre No 6′. The objective of this paper is to highlight and discuss those contradictions, which can be illustrated by the technical machine-streets conceived for the Ville Contemporaine of 1922 versus the V4 streets formulated in 1947 to reconcile with traditional streets.